Effect of coenzyme-q10 in the post-curettage against probing depth, relative attachment loss, and bleeding on probing - Aprilia Yuanita ANWARİSTİ (Journal of Syiah Kuala Dentistry Society, 2020)
The mechanical approach is one of the methods for periodontal disease treatment. Besides, medicine also was administered locally to reduce the number of pathogens present in the pocket. Coenzyme Q10 gel has low toxicity, biodegradable, prolongs drug release, and can accelerate tissue healing. The curettage action aims to establish adhesion intensity and remove calculus, bacteria, and granulation tissue. This study aimed to evaluate the effect of coenzyme Q10 gel on chronic periodontitis with curettage in relation to the probing depth (PD), relative attachment level (RAL) and bleeding on probing (BOP). The study sample consisted of 10 patients with curettage treatment and coenzyme Q10 gel application. The gel was applied to the pocket of chronic periodontitis patients after curettage. PD, RAL, and BOP of patients measured before and on days 21 and 30 after gel application. The results showed that there was a significant difference in BOP between observation times. There are differences in the reduction of PD and RAL. Coenzyme Q10 gel's application affected decreasing probing depth, relative attachment loss, and bleeding on probing after curettage